KITAB KUNING DAN TRADISINYA DI INDONESIA - Fajar Alfinur, Muhammad (SIWAYANG Journal: Publikasi Ilmiah Bidang Pariwisata, Kebudayaan, dan Antropologi, 2024)
This article was created with the aim of knowing the history of the yellow book and its traditions in Indonesia, especially in Islamic boarding schools. This yellow book is a book that has yellow paper written in Arabic and is a book that revolves around Islamic knowledge, both sharia and non-sharia. This research was carried out by collecting data from the library as a reference source. The research results show that the yellow book has a long historical record in Indonesia, especially in Islamic boarding schools. Although there is no certainty regarding the history of the yellow book being used as a reference in studying knowledge in Islam, the yellow book has become a curriculum in Islamic boarding schools in Indonesia. The yellow book is used as the main teaching material in teaching various Islamic disciplines such as fiqh, monotheism, tafsir, hadith, and Sufism, as well as tool sciences such as nahwu and shorof. Apart from that, the yellow book also reflects a strong Islamic identity and is a symbol of Islamic intellectual heritage in the archipelago. With the yellow book, Islamic scientific traditions in Islamic boarding schools can be preserved and developed from generation to generation. This research also found that the yellow book has an important role in forming the character and knowledge of students in Islamic boarding schools.